Kontribusi Nahdlatul Ulama terhadap Eksistensi Pendidikan di Indonesia 1929-1973 - Abdullah , A. Fatikhul Amin; Iskandar, Mohammad; Muhammad Hadiatur Rahman (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2024)
This research is motivated by the assumption that Nahdlatul Ulama is an organization that is not concerned with education. Whereas several contributions have been made by Nahdlatul Ulama in participating in advancing national education in Indonesia. This research proves the contribution of Nahdlatul Ulama to the current national education structure. For this reason, the method used is the historical research method and the method for collecting data with document studies, literature studies, and observation,. This study uses Anthony Giddens' structuration theory of agent, agency, structure, and duality of structure. This research produces evidence that the birth of the Joint Decree of Three Ministers is one part of the effort to recognize Islamic education by the state by accommodating existing madrasas for the pioneers of Nahdlatul Ulama figures as agents of change from the existing structure. Penelitian ini dilatarbelakangi adanya adanya anggapan Nahdlatul Ulama merupakan organisasi yang tidak konsen terhadap Pendidikan. Padahal terdapat beberapa kontribusi yang telah dilakukan Nahdlatul Ulama dalam ikut serta memajukan Pendidikan nasional di Indonesia. Metode yang digunakan adalah metode penelitian sejarah dan metode untuk mengumpulkan data dengan studi dokumen, studi literatur, observasi,. Studi ini menggunakan teori strukturasi Anthony Giddens tentang agen, agensi, struktur, dan dualitas struktur. Penelitian ini menghasilkan satu bukti bahwa lahirnya Surat Keputusan Bersama Tiga Menteri merupakan salah satu bagian dari upaya diakuinya Pendidikan Islam oleh negara dengan mengakomodir madrasah yang ada atas pelopor para tokoh Nahdlatul Ulama sebagai agen perubahan dari struktur yang ada.